Roles of fibroblast growth factor 21 in the control of depression‐like behaviours after social defeat stress in male rodents. (1st September 2021) - Usui, Naoki; Yoshida, Masahide; Takayanagi, Yuki; Nasanbuyan, Naranbat; Inutsuka, Ayumu; Kurosu, Hiroshi; Mizukami, Hiroaki; Mori, Yoshiyuki; Kuro‐o, Makoto; Onaka, Tatsushi
Abstract: Fibroblast growth factor 21 (FGF21) modulates energy metabolism and neuroendocrine stress responses. FGF21 synthesis is increased after environmental or metabolic challenges. Detailed roles of FGF21 in the control of behavioural disturbances under stressful conditions remain to be clarified. Here, we examined the roles of FGF21 in the control of behavioural changes after social defeat stress in male rodents. Central administration of FGF21 increased the number of tyrosine hydroxylase‐positive catecholaminergic cells expressing c‐Fos protein, an activity marker of neurones, in the nucleus tractus solitarius and area postrema. Double in situ hybridisation showed that some catecholaminergic neurones in the dorsal medulla oblongata expressed β‐Klotho, an essential co‐receptor for FGF21, in male mice. Social defeat stress increased FGF21 concentrations in the plasma of male mice. FGF21‐deficient male mice showed social avoidance in a social avoidance test with C57BL/6J mice (background strain of FGF21‐deficient mice) and augmented immobility behaviour in a forced swimming test after social defeat stress. On the other hand, overexpression of FGF21 by adeno‐associated virus vectors did not significantly change behaviours either in wild‐type male mice or FGF21‐deficient male mice. The present data are consistent with the view that endogenous FGF21, possibly during the developmental period, has an inhibitory action on stress‐induced depression‐like behaviour in male rodents. Abstract : Social defeat stress increased plasma concentrations of FGF21. Catecholaminergic neurones in the nucleus tractus solitarius and area postrema expressed β‐Klotho, an essential co‐receptor for FGF21, and were activated by social defeat stress and FGF21 administration. FGF21‐deficient mice showed augmented depression‐related behaviours after social defeat stress.